Participation of Africa to global agricultural trade AATM 2021 - Sall, Leysa Maty (2021)
Leysa Maty Sall POLICY SEMINAR Making the most of intra-African trade: the 2021 Africa Agriculture Trade Monitor Co-Organized by IFPRI and AKADEMIYA2063 SEP 23, 2021 - 09:30 AM TO 11:00 AM EDT